När olika professioner möts : En kvalitativ studie om sjukvårdskuratorer i tvärprofessionella team inom hälso- och sjukvård - Ademi,Valmire (2017)
When different professions meet – a qualitative study of healthcare counselors in interprofessional teams within the healthcare The purpose of this qualitative study was to investigate the experiences of healthcare counselors associated with interdicplinary team work in health care and what is considered important factors for the development of the profession itself. This research is based on 7 interviews with healthcare counselors. Empirical data have been collected from semi-structured interviews. The research was analyzed through organization theory, based on the political perspective, and also a professionalization theory. The result shows that the counsellors experience that their work and knowledge is valued at the hospital. In some aspects they show that their professional role is perceived as unclear and diffuse. The interdisciplinary team work provide several benefits between different professions coordinating their knowledge and resources. Interdisciplinary teams comes with some difficulty mainly in terms of status differences between professions which can cause conflicts of interest. The conclusion from the study is that the counselors can get a strong position in the hospital if they reinforces their knowledge more in the therapeutic topic. Otherwise would introduction of a future license for healtcare counselors be another way to have a stronger professional status within health and social care.
Keywords: Interprofessional teams; health care counselor; collaboration at hospital; interaction between diffrent professions; multi professional teamwork; health and social care.